Pengenalan Makroinvertebrata Bentik sebagai Bioindikator Pencemaran Perairan Sungai pada Siswa di Wonosalam, Mojokerto, Jawa Timur - Nirmala Fitria Firdhausi (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2019)
The river in Wonosalam is upstream of the rivers that flow in the Mojokerto and Jombang regions. As an upstream area, monitoring water quality of the river is needed so that pollution can be detected early. Water quality monitoring activities can be carried out using benthic macroinvertebrates indicator. The purpose of this PKM activity was to introduce water quality monitoring methods used benthic macroinvertebrates as bioindicators for students in the Wonosalam sub-district area. The main target of this activity is students of SLTPN 1 Wonosalam. The method used was lecturing, direct practicing, and discussion. Introduction of the benthic macroinvertebrates as a bioindicator was carried out very well: the students were very enthusiastic in the implementation activities from beginning to end, the students were quite active in the sampling process until the identification process, there was an increase in the students knowledge about bioindicators and the students were able to distinguish groups, EPT (Ephemeroptera, Plecoptera, and Trichoptera) and non-EPT. Based on benthic macroinvertebrate sampling the result showed that the value of the Sumber Bengawan river are 6.25, indicated that Sumber Bengawan river was not polluted.